An organic electroluminescent device

CN122995508APending Publication Date: 2026-10-27NANJING TOPTO MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611010257.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-08
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]随着OLED产业向大尺寸、高世代产线发展,下游厂商对生产成本愈发敏感,氘代率高的方案在商业竞争力上受到制约

Benefits of technology

1)本发明在有机电致发光器件的结构设计中,采用了具有折射率梯度的双层空穴传输层构型,通过特定的高折射率空穴传输材料层的插入和替代,优化了器件内的光场分布,以减少光子能量在有机层内部的无效损耗,提升器件光提取效率;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122995508A_ABST
    Figure CN122995508A_ABST
Patent Text Reader

Abstract

The application discloses an organic electroluminescent device, comprising an anode, a cathode and at least one light-emitting layer arranged between the anode and the cathode, wherein a hole injection layer, a first hole transport layer and a second hole transport layer are arranged between the anode and the light-emitting layer, the material forming the first hole transport layer is selected from a compound as shown in formula 1, the material forming the second hole transport layer is selected from a compound as shown in formula 2, and the refractive index of the first hole transport layer is higher than that of the second hole transport layer; (formula 1); (formula 2); the organic electroluminescent device adopts a double-layer hole transport layer configuration with a refractive index gradient, the light field distribution in the device is optimized by inserting and replacing a specific high-refractive-index hole transport material layer, the invalid loss of photon energy in the organic layer is reduced, and the light extraction efficiency of the device is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of organic electroluminescence technology, and specifically relates to an organic electroluminescent device. Background Technology

[0002] In organic light-emitting diodes (OLEDs), holes and electrons are injected from the anode and cathode, respectively, and meet in the light-emitting layer to form excitons, which then emit light to achieve the purpose of display. Due to their simple structure, low driving voltage, good flexibility, and ability to achieve large-area displays, OLEDs have been widely used in the field of light emission and lighting. However, OLEDs also have various light loss mechanisms, resulting in an external quantum efficiency that is much lower than the internal quantum efficiency. For conventional OLEDs, most photons are lost internally, with only a small portion of the light energy escaping into the air. To improve light extraction efficiency, existing technologies generally optimize device performance through improvements in materials and device structure. Among these, the design of optimizing light extraction by introducing organic layers with different refractive indices has received considerable attention in recent years.

[0003] Combining organic layers with different refractive indices can modulate the light propagation path within the device, thereby reducing photon energy loss after optimization. Patent documents such as CN116761868A ("Organic Electroluminescent Element, Organic Electroluminescent Display Device and Electronic Equipment") and CN122094393A ("Organic Electroluminescent Device and Display Equipment") both involve research on the refractive index matching of organic layers within the device. Meanwhile, in some existing technologies, introducing deuterated materials is a common strategy to improve the performance of the hole transport layer. The introduction of deuterium can alter molecular vibrational energy levels, which to some extent is beneficial for improving device lifetime and luminous efficiency. However, the introduction of deuterium also significantly increases the production cost of the material, especially the synthesis process that introduces deuterium at multiple specific locations.

[0004] As the OLED industry moves towards larger sizes and higher generation production lines, downstream manufacturers are becoming increasingly sensitive to production costs, and solutions with high deuteration rates are facing constraints in terms of commercial competitiveness. How to optimize costs and processes while maintaining good luminous efficiency is a technical issue worthy of further research. Summary of the Invention

[0005] The present invention aims to provide an organic electroluminescent device with a refractive index gradient, which has a novel innovative concept, in order to improve device performance or optimize cost or process.

[0006] To achieve the above-mentioned technical objectives, the technical solution provided by the present invention includes the following aspects: An organic electroluminescent device includes an anode, a cathode, and at least one light-emitting layer disposed between the anode and the cathode. A hole injection layer, a first hole transport layer, and a second hole transport layer are disposed between the anode and the light-emitting layer. The material forming the first hole transport layer is selected from the compound shown in Formula 1 below, and the material forming the second hole transport layer is selected from the compound shown in Formula 2 below, and the refractive index of the first hole transport layer is higher than the refractive index of the second hole transport layer; Formula 1 ; In Formula 1, R1 is selected from C1-C4 alkyl groups that are substituted with deuterium or not, L is a direct bond or a phenylene group, and Ar1 and Ar2 are each independently selected from C6-C12 aryl groups. Formula 2 ; In Equation 2: R2, R3, R4 and R5 each independently represent deuterium, deuterated or unsubstituted C1-C4 alkyl groups, i is an integer selected from 0 to 3, j, k and t each independently represent an integer selected from 0 to 4, and the number of deuterated or unsubstituted C1-C4 alkyl groups in R2, R3, R4 and R5 does not exceed 2. R6, R7, R8 and R9 each independently represent C1-C4 alkyl groups that are substituted with deuterium or not substituted. The same or different n, m, s and q represent 0 or 1, and n+m ≦2, s+q ≦2. The compound of formula (2) contains at least one C1-C4 alkyl group that is either deuterated or unsubstituted.

[0007] Based on the above solutions, more preferred technical solutions include: Furthermore, in Equation 1, Ar1 and Ar2 are the same C6-C12 aryl group.

[0008] Furthermore, in Formula 1, Ar1 and Ar2 are phenyl or biphenyl.

[0009] Furthermore, in Formula 1, the R1 group is located at the ortho or para position of L.

[0010] Furthermore, the material forming the first hole transport layer is selected from compounds shown in Formula 1-1: Equation 1-1 ; In Formula 1, R1 is selected from deuterated or unsubstituted methyl groups, L is a direct bond or phenylene, and Ar1 and Ar2 are each independently selected from C6-C12 aryl groups.

[0011] Furthermore, in Formula 1-1, Ar1 and Ar2 are identical and represent phenyl or biphenyl.

[0012] Furthermore, in Formula 2, at least one of R6 and R7 is an alkyl or deuterated alkyl group.

[0013] Furthermore, in Equation 2: When R2 is a deuterated or unsubstituted alkyl group, i is 1; When R3 is a deuterated or unsubstituted alkyl group, j is 1; When R4 is a deuterated or unsubstituted alkyl group, k is 1; When R5 is a deuterated or unsubstituted alkyl group, t is 1.

[0014] Furthermore, in Formulas 1 and 2, the deuterium-substituted or unsubstituted C1-C4 alkyl group is selected from deuterium-substituted or unsubstituted methyl or tert-butyl groups.

[0015] Furthermore, the material forming the first hole transport layer is selected from one of the following compounds: .

[0016] Furthermore, the material forming the second hole transport layer is selected from one of the following compounds: .

[0017] Beneficial effects: 1) In the structural design of organic electroluminescent devices, this invention adopts a double-layer hole transport layer configuration with a refractive index gradient. By inserting and replacing a specific high-refractive-index hole transport material layer, the light field distribution within the device is optimized to reduce the ineffective loss of photon energy inside the organic layer and improve the light extraction efficiency of the device. 2) In the organic electroluminescent device of the present invention, the first hole transport layer with high refractive index is a carbazole aromatic amine material modified by alkyl or deuterated alkyl groups, which can effectively suppress the crystallization tendency of molecules, promote the formation of a uniform and stable amorphous film, and improve the long-term stability of the device. Moreover, this modification can fine-tune the energy level structure of the material, optimize the charge injection and transport process, and improve the energy level matching with adjacent functional layers. The second hole transport layer is selected from a monoamino aromatic amine material with large steric hindrance. Its rigid non-planar configuration can effectively suppress the close packing between molecules, reduce the crystallization tendency, and thus ensure the uniformity and stability of film formation. 3) By improving the materials used in the device film layer, this invention improves the performance of organic electroluminescent devices in one or more aspects of luminous efficiency, voltage, and lifetime compared to devices with unmodified first hole transport layer materials, or further reduces material costs or achieves results through a simpler process compared to existing technologies that introduce deuterated modification of the first hole transport layer material in other specific ways to achieve similar device performance. Attached Figure Description

[0018] Figure 1 This is a schematic diagram of the structure of the organic electroluminescent device of the present invention; Figure 2 This is the HPLC chromatogram of compound 1 of the present invention; Figure 3 This is the HPLC chromatogram of compound 149 of the present invention.

[0019] Figure 1 The reference numerals in the figures represent: 1-anode, 2-hole injection layer, 3-first hole transport layer, 4-second hole transport layer, 5-electron blocking layer, 6-first light-emitting layer, 7-second light-emitting layer, 8-hole blocking layer, 9-electron transport layer, 10-electron injection layer, 11-cathode. Detailed Implementation

[0020] Embodiments of various aspects of the invention are further described and illustrated below. It should be understood that the following description is not intended to limit the claims to the specific aspects described. Rather, it is intended to cover substitutions, modifications, and equivalents that may be included within the scope defined by the appended claims.

[0021] In this article, the terms "substituted" and "unsubstituted" refer to the recoordination of at least one hydrogen atom of a group with a substituent group such as deuterium or aryl. The term "aryl" in this article refers to a group containing one or more aromatic rings, including but not limited to benzene, naphthalene, phenanthrene, fluorene, and acenaphthene.

[0022] The terms C1-C4 and C6-C12 in the text indicate that the modified groups contain 1-4 and 6-12 carbon atoms, respectively. If the corresponding groups can be substituted, C1-C4 and C6-C12 here do not include the number of carbon atoms of the substituents.

[0023] In this invention, "deuterium" refers to a stable isotope of hydrogen, also known as heavy hydrogen, and its element symbol is D.

[0024] The following describes the implementation method of the present invention in more detail with reference to the synthesis and testing of materials, as well as to verify the progressiveness of the design scheme. For the corresponding embodiments, if specific conditions are not specified, they shall be carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments used are not specified, they are all conventional products that can be purchased commercially.

[0025] I. Synthesis of HTL1 material 1. Synthesis of Compound 2

[0026] 1.1 Synthetic Route ; 1.2 Synthesis Process S1: Under nitrogen protection, compound 2-a (1 eq, 16.76 g, 336.23 g / mol, 49.85 mmol), sodium tert-butoxide (1 eq, 4.79 g, 96.1 g / mol, 49.85 mmol), and deuterated dimethyl sulfoxide (10 eq, 41.96 g, 84.17 g / mol, 498.47 mmol) were added to a reaction flask. After the addition was complete, the mixture was heated to 80 °C and stirred for 48 h. After the reaction was complete, the mixture was cooled to room temperature, 1 L of water was added, and the mixture was stirred to crystallize for 2 h. The crystals were then filtered and dried to obtain compound 2-b (14.91 g, yield 88.21%). S2: Under nitrogen protection, compound 2-b (1 eq, 14.91 g, 339.2 g / mol, 43.96 mmol), compound 2-c (1.02 eq, 12.96 g, 289.14 g / mol, 44.84 mmol), potassium carbonate (2 eq, 12.15 g, 138.21 g / mol, 87.91 mmol), tetraphenylphosphine palladium (0.02 eq, 1.02 g, 1155.56 g / mol, 0.879 mmol), and toluene / ethanol / water (140 mL / 70 mL / 43 mL) were added to the reaction flask. After the addition was complete, the temperature was raised to 80 °C and the mixture was stirred for 12 h. After the reaction was complete, ethanol (300 mL) and water (50 mL) were added. The solution was cooled to room temperature and stirred for 2 hours to induce crystallization. The mixture was then filtered, and the filter cake was recrystallized four times with toluene / ethanol. After filtration and drying, compound 2 (14.43 g, yield 65.2%) was obtained. ESI-MS (m / z, [M+H)) was performed. + Theoretical value: 504.25, measured value: 504.21. 2. Synthesis of Compound 1

[0027] 2.1 Synthetic Route ; 2.2 Synthesis Process Compound 1 was prepared using a similar method to step 2 of compound 2, yielding a yield of 68.4%. ESI-MS (m / z, [M+H]) was used to analyze the reaction. + Theoretical value: 501.24, measured value: 501.35. 3. Synthesis of Compound 3

[0028] 3.1 Synthetic Route ; 3.2 Synthesis Process Compound 3 was prepared using a similar method to step 2 of compound 2, with a yield of 56.1%. ESI-MS (m / z, [M+H]) yielded the compound. +Theoretical value: 501.24, measured value: 501.26. 4. Synthesis of Compound 4

[0029] 4.1 Synthetic Route ; 4.2 Synthesis Process Compound 4 was prepared using a similar method to that used for compound 2, with a yield of 62.3%. ESI-MS (m / z, [M+H]) yielded the compound. + Theoretical value: 504.25, measured value: 504.39. 5. Synthesis of other compounds

[0030] Other compounds of the present invention used in the first hole transport layer can also be prepared by similar preparation methods, referring to the overall or partial synthetic route of compound 2, and will not be listed here one by one.

[0031] 2. HTL2 material synthesis 1. Synthesis of Compound 149

[0032] 1.1 Synthetic Route ; 1.2 Synthesis Process S1: Under nitrogen protection, compound 149-a (1 eq, 27.32 g, 273.17 g / mol, 0.1 mol), compound 149-b (1 eq, 18.33 g, 183.25 g / mol, 0.1 mol), sodium tert-butoxide (1.5 eq, 14.42 g, 96.1 g / mol, 0.15 mol), 10% tri-tert-butylphosphine toluene solution (0.04 eq, 8.1 ml, 202.32 g / mol, 0.004 mol), tris(dibenzylacetone)palladium (0.02 eq, 1.83 g, 915.7 g / mol, 0.002 mol), and toluene (300 mL) were mixed. Add ethanol (mL) to the reaction flask. After the addition is complete, heat to 110℃ and stir for 6 hours. After the reaction is complete, filter the mixture while hot through silica gel. Wash the filter cake with dichloromethane. Concentrate the filtrate under reduced pressure to dryness. Add ethanol (150 mL), heat to 80℃ and stir to dissolve. Cool to room temperature and crystallize for 5 hours. Filter to obtain a gray solid. Dry the solid at 85℃ to obtain compound 149-c (28.5 g, yield 75.9%). S2: Under nitrogen protection, compound 149-c (1 eq, 28.5 g, 375.51 g / mol, 75.9 mmol), compound 1-b (1 eq, 30 g, 395.3 g / mol, 75.9 mmol), sodium tert-butoxide (1.5 eq, 10.94 g, 96.1 g / mol, 0.11 mol), 10% tritert-tert-butylphosphine toluene solution (0.04 eq, 6.1 ml, 202.32 g / mol, 3.04 mmol), tris(dibenzylacetone)palladium (0.02 eq, 1.39 g, 915.7 g / mol, 1.52 mmol), and toluene (300 mL) were mixed. Add mL of the mixture to the reaction flask. After the addition is complete, heat to 110℃ and stir for 6 hours. After the reaction is complete, filter the mixture while hot through silica gel. Wash the filter cake with dichloromethane. Concentrate the filtrate to dryness under reduced pressure. Add toluene (150 mL) and heat to dissolve the solid. Add ethanol (150 mL) and cool to room temperature for 2 hours to allow crystallization. Recrystallize the obtained solid twice with toluene (150 mL) + ethanol (150 mL). Recrystallize the obtained solid twice with toluene (75 mL). Dry the obtained solid at 85℃ to give compound 149 (31.2 g, yield 59.6%). ESI-MS (m / z, [M+H)) + Theoretical value: 690.32, measured value: 690.33. 2. Synthesis of Compound 157

[0033] 2.1 Synthetic Route ; 2.2 Synthesis Process Compound 157 was prepared using a similar method to that used for compound 149. The reaction yielded 60.3% of the compound. ESI-MS (m / z, [M+H]) + Theoretical value: 802.44, measured value: 802.45. 3. Synthesis of Compound 165

[0034] 3.1 Synthetic Route ; 3.2 Synthesis Process Compound 165 was prepared using a similar method to that used for compound 149. The reaction yielded compound 165 (62% yield). ESI-MS (m / z, [M+H]) + Theoretical value: 746.38, measured value: 746.36. 4. Synthesis of Compound 173

[0035] 4.1 Synthetic Route ; 4.2 Synthesis Process Compound 173 was prepared using a similar method to that used for compound 149. The reaction yielded 58.2% (ESI-MS, m / z, [M+H)). + Theoretical value: 690.32, measured value: 690.30. 5. Synthesis of Compound 177

[0036] 5.1 Synthetic Route ; 5.2 Synthesis Process Compound 177 was prepared using a similar method to that used for compound 149. The reaction yielded 60.5% of the compound. ESI-MS (m / z, [M+H]) + Theoretical value: 704.33, measured value: 704.29. 6. Synthesis of Compound 181

[0037] 6.1 Synthetic Route ; 6.2 Synthesis Process Compound 181 was prepared using a similar method to that used for compound 149. The reaction yielded compound 181 (59.8% yield). ESI-MS (m / z, [M+H]) + Theoretical value: 816.46, measured value: 816.45. 7. Synthesis of Compound 189

[0038] 7.1 Synthetic Route ; 7.2 Synthesis Process Compound 189 was prepared using a similar method to that used for compound 149. The reaction yielded compound 189 (63.3% yield). ESI-MS (m / z, [M+H]) + Theoretical value: 844.49, measured value: 844.47.

[0039] III. Device Fabrication

[0040] 1. Application Example 1 ITO / Ag / ITO was used as the anode substrate material for the reflective layer, and its surface was sequentially treated with water, acetone, and N2 plasma. A 10 nm layer of compound 1 doped with 3% NDP-9 was deposited on top of the ITO / Ag / ITO anode substrate to form a hole injection layer (HIL). A 46 nm layer of compound 1 was vacuum-deposited on top of the hole injection layer (HIL) to form a first hole transport layer (HTL1). A 52 nm layer of compound 157 was vacuum-deposited on top of the first hole transport layer (HTL1) to form a second hole transport layer (HTL2). EB-1 was vacuum-deposited on top of the second hole transport layer (HTL2) to form a 10 nm thick electron blocking layer (EBL). BH-1 was used as the host material and BD-1 was used as the dopant material (BD-1 doping ratio was 1% of the host material BH-1) for co-evaporation to form a first emitting layer (EML1) with a thickness of 5 nm on the electron blocking layer (EBL). BH-2 was used as the host material and BD-1 was used as the dopant material (BD-1 doping ratio was 2% of the host material BH-2) for co-evaporation to form a second emitting layer (EML2) with a thickness of 15 nm on the first emitting layer (EML1). HB-1 was then deposited onto the second emitting layer (EML2) to obtain a hole blocking layer (HBL) with a thickness of 5 nm. ET-1 and LiQ were then co-deposited onto the hole blocking layer (HBL) at a mass ratio of 5:5 to obtain a layer with a thickness of 30 nm. An electron transport layer (ETL) is formed; ytterbium (Yb) is deposited onto the ETL to form an electron injection layer (EIL) with a thickness of 1 nm; magnesium (Mg) and silver (Ag) are mixed in a 1:9 mass ratio and deposited onto the EIL to form a cathode with a thickness of 12 nm; a 60 nm thick CP-2 layer is deposited at the sealing layer of the cathode to form a light extraction layer (CPL); finally, the device surface is sealed with a UV-curable adhesive and a sealing film containing a desiccant to protect the organic electroluminescent device from atmospheric oxygen or moisture. This completes the fabrication of the organic electroluminescent device.

[0041] In this invention, the NDP-9 content in the hole injection layer is recommended to be controlled between 1% and 5% of the mass of the hole injection layer main material, preferably around 3%, and can be slightly adjusted according to the actual situation.

[0042] 2. Application Example 2-28 Based on Application Example 1, the material of the first hole transport layer HTL1 is replaced with compounds numbered 3, 11, 4 and 12 in Table 3 and / or Table 5, and the main material of the hole injection layer and the second hole transport layer HTL2 are replaced with compound 149, thereby obtaining the organic electroluminescent devices of Application Example 2, Application Example 4, Application Example 16 and Application Example 18. Based on Application Example 1, the material of the first hole transport layer HTL1 was replaced with compounds numbered 5, 2, and 6 in Table 3 and / or Table 5, respectively, to obtain the organic electroluminescent devices of Application Example 3, Application Example 15, and Application Example 17. Based on Application Example 1, the material of the first hole transport layer HTL1 is replaced with compounds numbered 13, 17, 21 and 22 in Table 3 and / or Table 5, respectively, and the main material of the hole injection layer and the second hole transport layer HTL2 are replaced with compound 165, thereby obtaining the organic electroluminescent devices of Application Examples 5 to 7 and Application Example 19. Based on Application Example 1, the material of the first hole transport layer HTL1 was replaced with compounds numbered 31, 28, and 50 in Table 3 and / or Table 5, respectively, and the main material of the hole injection layer and the second hole transport layer HTL2 were replaced with compound 173, thereby obtaining the organic electroluminescent devices of Application Example 8, Application Example 20, and Application Example 21. Based on Application Example 1, the material of the first hole transport layer HTL1 was replaced with compounds numbered 53, 57, and 58 in Table 3 and / or Table 5, respectively, and the main material of the hole injection layer and the second hole transport layer HTL2 were replaced with compound 177, thereby obtaining the organic electroluminescent devices of Application Example 9, Application Example 10, and Application Example 22. Based on Application Example 1, the material of the first hole transport layer HTL1 was replaced with compounds numbered 69, 78, and 84 in Table 3 and / or Table 5, respectively, and the main material of the hole injection layer and the second hole transport layer HTL2 were replaced with compound 181, thereby obtaining the organic electroluminescent devices of Application Example 11, Application Example 23, and Application Example 24. Based on Application Example 1, the material of the first hole transport layer HTL1 was replaced with compounds numbered 101, 111, 123 and 136 in Table 3 and / or Table 5, respectively, and the main material of the hole injection layer and the second hole transport layer HTL2 were replaced with compound 189, thereby obtaining the organic electroluminescent devices of Application Examples 12-14 and Application Example 25.

[0043] In addition to the compounds proposed in this invention, the structures of other compounds used in the above preparation process are shown in Table 1 below: Table 1

[0044] IV. Device Testing The following tests were conducted on the characteristics of organic electroluminescent devices, including the start-up voltage, luminous efficiency, and luminous lifetime. The luminous lifetime is defined as the T97% data, which is the relative time it takes for the device's luminous brightness to decrease to 97% of its initial brightness (with Comparative Example 2 as a reference).

[0045] 1. Test 1 Based on Application Example 1, 149, 157, 177, and 189 were used as the main material for the hole injection layer and the material for the hole transport layer, respectively, for vapor deposition. Here, the thickness of the hole transport layer film is equal to the sum of the thicknesses of the first and second hole transport layers in Application Example 1, in order to replace the first and second hole transport layer regions in Application Example 1, thus obtaining Comparative Examples 1-4.

[0046] Based on Application Example 1, the materials of the first hole transport layer and the second hole transport layer were replaced with D-1 and 157, D-2 and 165, D-3 and 181, D-4 and 58, D-5 and 177, and D-6 and 157 respectively for vapor deposition. The main material of the hole injection layer of each device was the same as that of the second hole transport layer, thus obtaining the organic electroluminescent devices of Comparative Examples 5-10.

[0047] The structures of comparative compounds D1-D6 are shown in Table 2 below: Table 2

[0048] The test results for Comparative Examples 1-10 and Application Examples 1-14 are shown in Table 3 below: Table 3

[0049] Based on the material type proposed in this invention, a comparison with the test data of Comparative Examples 1-4 shows that, compared with devices using a single material for the hole transport layer, the device of this invention, by setting a first hole transport layer and a second hole transport layer between the hole injection layer and the electron blocking layer, exhibits significantly improved device performance, including a significant decrease in startup voltage and improvements in luminous efficiency and lifetime. More specifically, the device of this invention replaces the front region of the original hole transport layer with a specific material layer with a higher refractive index, thereby optimizing the optical field distribution of the device microcavity and the energy loss of photons, thus improving device performance. As a more preferred embodiment, this invention recommends a material combination for the hole transport layer according to the formula "refractive index of the first hole transport layer - refractive index of the second hole transport layer ≥ 0.15", where the refractive index specifically refers to the value at a wavelength of 460 nm.

[0050] The device combinations in Comparative Examples 5-10 and 11 and 12 below are based on the combination concept of the similar patent application CN122094393A. A comparison of the test data from Application Example 1-14 and Comparative Example 5-10 shows that after introducing alkyl groups at specific positions in the first hole transport layer compound, the device performance exhibits better results in terms of startup voltage, luminous efficiency, and luminous lifetime.

[0051] 2. Test Two Based on Application Example 1, the materials of the first hole transport layer and the second hole transport layer are replaced with D-7 and 181 and D-8 and 177, respectively, while the main material of the hole injection layer is the same as that of the second hole transport layer, thus obtaining Comparative Examples 11 and 12.

[0052] The structures of comparative compounds D7-D8 are shown in Table 4 below: Table 4

[0053] The test results for Comparative Examples 11 and 12 and Application Examples 15-25 are shown in Table 5 below: Table 5

[0054] A comparison of the data in Tables 3 and 5 shows that, compared to the application examples in Table 3, the devices in Table 5, after introducing deuterium into the first hole transport layer material in two ways, exhibit varying degrees of optimization in one or more aspects of efficiency and lifetime.

[0055] Compared to Comparative Examples 11 and 12, Application Examples 1-14 modify the first hole transport layer material with methyl groups. Compared to the modification scheme that introduces deuterium, the cost of using this material can be reduced by several times, and compared to Comparative Examples 11 and 12, its device performance does not show a significant decrease in voltage and luminous efficiency.

[0056] Comparative Examples 11 and 12, and Application Examples 15-25, employed different methods to introduce deuterium. Compared to Application Examples 15-25, Comparative Examples 11 and 12 have more deuteration sites and a greater number of deuterations, expanding the stabilization range from specific points to a broader area. Based on existing technologies, further increasing the deuteration rate or the number of deuteration sites could potentially yield better device performance. However, this would also imply a more complex synthesis process, making production more complicated and significantly increasing production costs, making it unsuitable for customers with higher cost control requirements. Compared to Comparative Examples 11 and 12, the deuteration synthesis process of the first hole transport layer material in Application Examples 15-25 is relatively simple, which is beneficial for improving production efficiency and controlling costs. Furthermore, the Application Examples 15-25 devices exhibit better luminous efficiency and lifetime compared to the devices in Comparative Examples 11 and 12. Specifically, comparative examples 11 and 24, and comparative examples 12 and 22 can be compared horizontally. The first hole transport layer materials in the above comparative examples and application examples have the same core structure and other test conditions, which can more accurately reflect the optimization of the data.

[0057] In summary, compared with comparative examples 11-12 and similar technical solutions, the technical solution designed in this invention can effectively simplify the process steps, and the design that does not introduce deuterium can further significantly reduce the raw material cost.

[0058] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.

Claims

1. An organic electroluminescent device, comprising an anode, a cathode, and at least one light-emitting layer disposed between the anode and the cathode, wherein a hole injection layer, a first hole transport layer, and a second hole transport layer are disposed between the anode and the light-emitting layer, characterized in that: The material forming the first hole transport layer is selected from the compound shown in Formula 1 below, and the material forming the second hole transport layer is selected from the compound shown in Formula 2 below, and the refractive index of the first hole transport layer is higher than the refractive index of the second hole transport layer; Formula 1 ; In Formula 1, R1 is selected from C1-C4 alkyl groups that are substituted with deuterium or not, L is a direct bond or a phenylene group, and Ar1 and Ar2 are each independently selected from C6-C12 aryl groups. Formula 2 ; In Equation 2: R2, R3, R4 and R5 each independently represent deuterium, deuterated or unsubstituted C1-C4 alkyl groups, i is an integer selected from 0 to 3, j, k and t each independently represent an integer selected from 0 to 4, and the number of deuterated or unsubstituted C1-C4 alkyl groups in R2, R3, R4 and R5 does not exceed 2. R6, R7, R8 and R9 each independently represent C1-C4 alkyl groups that are substituted with deuterium or not substituted. The same or different n, m, s and q represent 0 or 1, and n+m ≦2, s+q ≦2. The compound of formula (2) contains at least one C1-C4 alkyl group that is either deuterated or unsubstituted.

2. The organic electroluminescent device as described in claim 1, characterized in that, In Equation 1, Ar1 and Ar2 are the same C6-C12 aryl group.

3. The organic electroluminescent device as described in claim 1, characterized in that, In Formula 1, Ar1 and Ar2 are phenyl or biphenyl.

4. An organic electroluminescent device as described in claim 1, characterized in that, In Formula 1, the R1 group is located at the ortho or para position of L.

5. An organic electroluminescent device as described in claim 1, characterized in that, The material forming the first hole transport layer is selected from the compounds shown in Formula 1-1 below: Equation 1-1 ; In Formula 1, R1 is selected from deuterated or unsubstituted methyl groups, L is a direct bond or phenylene, and Ar1 and Ar2 are each independently selected from C6-C12 aryl groups.

6. An organic electroluminescent device as described in claim 5, characterized in that, In Formula 1-1, Ar1 and Ar2 being the same represent phenyl or biphenyl.

7. An organic electroluminescent device as described in claim 1, characterized in that, In Formula 2, at least one of R6 and R7 is an alkyl or deuterated alkyl group.

8. An organic electroluminescent device as described in claim 1, characterized in that, In Equation 2: When R2 is a deuterated or unsubstituted alkyl group, i is 1; When R3 is a deuterated or unsubstituted alkyl group, j is 1; When R4 is a deuterated or unsubstituted alkyl group, k is 1; When R5 is a deuterated or unsubstituted alkyl group, t is 1.

9. An organic electroluminescent device as described in claim 1, characterized in that, In Formulas 1 and 2, the C1-C4 alkyl group, whether deuterated or unsubstituted, is selected from deuterated or unsubstituted methyl or tert-butyl groups.

10. An organic electroluminescent device as described in claim 1, characterized in that, The material forming the first hole transport layer is selected from one of the following compounds: 。 11. An organic electroluminescent device as described in claim 1, characterized in that, The material forming the second hole transport layer is selected from any of the following compounds: 。

Citation Information

Patent Citations

  • Organic electroluminescent element, organic electroluminescent display device, and electronic apparatus

    CN116761868A

  • Organic electroluminescent device and display equipment

    CN122094393A